A cholesterol-dependent switch controls organ-specific metastasis in pancreatic cancer - Haenlin, Julie; Schulze, Almut (Developmental cell, 2025)
As different organs offer distinct chemical microenvironments, cancer cells require unique metabolic adaptation to colonize distant sites. In a recent issue of Nature, Rademaker et al. identify PCSK9 as a predictive factor for metastatic colonization of different organs, showing adaptation of cancer cells to different environments by regulating cholesterol metabolism.